EFEKTIVITAS KOMUNIKASI POLITIK ERMA SURYANI RANIK (ANGGOTA DPD ASAL KALIMANTAN BARAT) DENGAN MASYARAKAT PERBATASAN DESA SEBUNGA KECAMATAN SAJIGAN BESAR - FITRIYASA, FITRIYASA (Politika: Jurnal Ilmu Politik, 2014)
This research describing how political communication effectiveness been maintained between members DPD RI origin West Kalimantan and local communities border. Political communication that develops between the two not widely held in official. But it is not seen in border West Kalimantan namely village Sebunga West Kalimantan. DPD RI as an institution regional representatives should have a place communication between DPD members and a constituent at each region. It is embodied in public consultation forum border area that in cooperation LSM Perhimpunan PENA an NGO local as an escort the forum.Communication that lasts imaged in public consultation forum border areas. Communication effectiveness Erma Suryani Ranik can be assessed of credibilityÂ  communicator, structure messages, media, society and reaction that is in communication process political. Keyword : The effectiveness of political communication, DPD RI members West Kalimantan, the community border.